2017
DOI: 10.17533/udea.ikala.v22n02a09
|View full text |Cite
|
Sign up to set email alerts
|

The phonetics and phonology of Eastern Andalusian Spanish: A review of literature from 1881 to 2016

Abstract: Despite previous studies on Eastern Andalusian Spanish, interest in this geolect boomed only after the theory of vowel doubling was posited for this variety of Spanish. According to this theory, in Eastern Andalusian Spanish, vowels preceding /s/ aspiration or deletion change their quality and, as a result, carry the semantic function of /s/. Since then, many researchers have studied the vowel and consonant systems of this variety of Spanish and the phoneticphonological debate is still ongoing. This article re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The present article has analysed the perception of words with and without underlying word-final /s/ in EAS. As explained in Herrero de Haro ( , 2017aHaro ( , 2017b,…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The present article has analysed the perception of words with and without underlying word-final /s/ in EAS. As explained in Herrero de Haro ( , 2017aHaro ( , 2017b,…”
Section: Resultsmentioning
confidence: 93%
“…Several theories have been suggested to describe the phonetic-phonological system of EAS (presented in detail in Herrero de Haro (2017b). Amongst many others, there are two recurring theories refuting phonemic desdoblamiento: 1) context is needed to perceive deleted /s/ (López Morales 1984); and 2) vowel-harmony (not just word-final vowel opening) needs to be present to identify when /s/ has been deleted (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sibilant fricatives and affricates have been studied broadly within Romance (Recasens and Espinosa 2007) and other typologically distinct languages (Gordon et al 2002). Within Peninsular Spanish, several variable phenomena have been identified that are relevant to the Spanish post-alveolar affricate, although focus is usually placed upon deaffrication in the speech of elderly, rural speakers (e.g., Henríquez-Barahona and Fuentes-Grandón 2018; Herrero de Haro 2017b;Samper-Padilla 2011). Alongside production of /tS/ (e.g., in hecho [hetSo] 'made/did') as the deaffricated Andalusian [S] (e.g., [heSo]; Villena-Ponsoda 2013), researchers have also identified a voiced post-palatal [dZ] in the Canary Islands (e.g., [hedZo]; Almeida 2019) and a voiced pre-palatal [Ã] in Murcia (e.g., [heÃo]; Torrano Moreno 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, different scholars have proposed surface vowel systems for EAS that vary from eight vowels (e.g., Navarro Tomás 1938, 1939 to fourteen vowels (Herrero de Haro, 2019c). More information on EAS vowel opening can be found in Herrero de Haro (2017bHaro ( , 2023 and Herrero de Haro and Hajek (2022).…”
Section: Introductionmentioning
confidence: 99%